Computational Fluid Dynamics (CFD) Simulation of Mixing Tank at Milk Powder Factory to Reduce Material Losses - Agus Surono; Achmad Dwitama Karisma; Muchamad Kurniawan Dwi Febrianto; Fitriah Dwi Mulyani; Daril Ridho Zuchrillah (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2023)
Industrial milk powder production applies the principle of a spray dryer. In the powdered milk industry using a spray dryer, there are still some problems in actual conditions such as fouling in the heat exchanger and losses. Losses are lost material or time so that result in losses for the company. The importance of finding material losses as soon as possible it is possible to make a solution so that initially unknown material is wasted in vain can be used as a finished good. Steps taken to resolve the problem material losses is to identify problems and data by making mapping losses according to actual conditions. After that, a CFD mixing tank simulation can be performed on Ansys with the aim of the simulation is to get the contour of the foaming phenomenon and find out the height the phenomenon of foaming (foam) with the properties set up begins at the beginning of making geometric designs with the size of the tank is 3.5 m and uses a marine propeller type, then proceeds with meshing In geometry, meshing here uses the automatic meshing method due to the limited analysis students. after that the solving stage is carried out by inputting data such as density, viscosity and input multiphase (mixture), viscous (Large Eddy Simulation), as the boundary conditions of the geometry, after that by making a plane from the results of running to form a plane in geometry, then choose the results of the contour volume fraction to find out the phenomena that occur in mixing tank so that conclusions and solutions can be drawn. Based on the results of data analysis and the field in the form of mapping and data on quantity losses, there are still some material losses in the form of wet and dry losses that have not been identified, initially the percentage ratio of material losses is 40.57% to 9%. One of the biggest contributors to material wet losses is mixing tanks which simulated until it is known that there is a foaming phenomenon. It interferes with the way it works level sensor which causes less maximum withdrawal of milk liquid by the pump. The best solution right way to reduce losses that occur in the mixing tank is to close the valve mixing tank output when showing 1.8% or can be rounded to 2% for safety pump. The liquid that is used as a product is 270 liters which is equivalent to 113 kg. If the calculation is carried out, the company can store 8,505 kg/month of powder.